2010
DOI: 10.1074/jbc.m110.105387
|View full text |Cite
|
Sign up to set email alerts
|

Tau Potentiates Nerve Growth Factor-induced Mitogen-activated Protein Kinase Signaling and Neurite Initiation without a Requirement for Microtubule Binding

Abstract: Microtubule-associated protein Tau is known to bind to and stabilize microtubules, thereby regulating microtubule dynamics. However, recent evidence has indicated that Tau can also interact with various components of intracellular signaling pathways, leading to the possibility that Tau might have a role in signal transduction. Here we provide evidence that during growth factor stimulation of neuronal cells, Tau has functions in advance of the neurite elongation stage. Using Tau-depleted neuronal cell lines, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 90 publications
4
79
0
Order By: Relevance
“…These include the appearance of apoptotic and mitotic markers in "pre-tangle" neurons [155][156][157] and the activation of developmentassociated signal transduction pathways resulting in aberrant cellular changes normally associated with development, such as neuropil thread formation [17,19,241,242]. Tau kinases such as CDK5, GSK3β and Mark1 normally play critical roles in cell cycle control, establishment of neuronal polarity and axonal outgrowth [243][244][245][246], so their roles in tau toxicity may therefore be due to aberrant activation of these same functions during the course of AD pathogenesis [147,[247][248][249] 3b Dendritic tau accumulation leads to tau secretion via multiple mechanisms…”
Section: Predisposing Risk Factors To the Development Of Loadmentioning
confidence: 99%
“…These include the appearance of apoptotic and mitotic markers in "pre-tangle" neurons [155][156][157] and the activation of developmentassociated signal transduction pathways resulting in aberrant cellular changes normally associated with development, such as neuropil thread formation [17,19,241,242]. Tau kinases such as CDK5, GSK3β and Mark1 normally play critical roles in cell cycle control, establishment of neuronal polarity and axonal outgrowth [243][244][245][246], so their roles in tau toxicity may therefore be due to aberrant activation of these same functions during the course of AD pathogenesis [147,[247][248][249] 3b Dendritic tau accumulation leads to tau secretion via multiple mechanisms…”
Section: Predisposing Risk Factors To the Development Of Loadmentioning
confidence: 99%
“…Therefore, a modified pattern of tau isoform expression/ratio, due to tau aggregation for instance, may profoundly affect the axonal transport and could possibly lead to neurodegeneration (Crosby AH, 2003). Besides its known role as a microtubule-stabilizer and organizer, tau may exert several other functions as signalling pathway in neurons (Ittner LM et al, 2010 andLeugers CJ, 2010) and DNA protection under stress stimuli . A unique human tau (MAPT) gene is located on chromosome 17 at the band position 17q21.…”
Section: Tau Proteinsmentioning
confidence: 99%
“…26 Phosphorylation at Thr-231 is important for the ability of Tau to enhance mitogen-activated protein kinase-induced NGF response. 27 Besides, serine 202, threonine 205 and threonine 231 can be phosphorylated by GSK-3. 28 To verify that Tau phosphorylation, and not synthesis, was affected by lithium, blots were analyzed with Tau5, a phosphorylation-independent antibody that recognizes total Tau.…”
Section: Real-time Rt-pcr Of Ngfmentioning
confidence: 99%
“…Tau has been shown to play a role in neurite length and neurite initiation. 27 Tau phosphorylation influences the positioning of Tau in dendrites, and the association of Tau with plasma membranes and nuclei. Previous studies have shown that phosphorylation of Tau at Thr-231 is required to potentiate activation of activator protein-1 transcription factors, an element of NGF promoter, through the mitogen-activated protein kinase pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation